Persepsi Guru Terhadap Pelaksanaan Asesmen Kompetensi Minimum Berbasis Komputer - Kusmilawati, Febriana (Journal of Innovation in Teaching and Instructional Media, 2024)
This study aims to determine teachers’ perceptions of the results of Computer-Based Minimum Competency Assessment Program (ANBK) at SDN 143 Palembang so that they can determine the school’s readiness to participate in ANBK in 2024. This study uses qualitative descriptive research taken through observation, interviews, and documentation activities. The data sources in this study were grade V teachers and 10 grade V students at SDN 143 Palembang. The findings in this research activity were the lack of students’ abilities in literacy and numeracy aspects. The results of this research activity are about the implementation of the ANBK and how teachers develop a learning framework so that students can improve their literacy and numeracy skills to better prepare themselves for the next ANBK implementation. Research like this has been conducted before by other researchers, but the respondents and implementers were different, and this is the first case study to thoroughly study the use of computer-based ANBK at SDN 143 Palembang. This study is expected to provide specific recommendations for schools to improve the implementation of ANBK. They can also help in making educational policies that are more in line with the needs of students in the digital era.